An evaluation of critical heat flux prediction methods for the upward flow in a vertical narrow rectangular channel. (October 2021) - Yan, Meiyue; Ma, Zaiyong; Pan, Liangming; Liu, Wei; He, Qingche; Zhang, Rui; Wu, Qi; Xu, Wangtao
Abstract: Narrow rectangular channels have widespread application in various domains owing to their significant enhancement in boiling heat transfer. In the present work, the CHF (critical heat flux) prediction method has been comprehensively evaluated and analyzed by the experimental data covering wide operating conditions in narrow rectangular channels. The Bubble Crowding Model can predict the high critical heat flux region. The prediction deviation of ANN (Artificial Neural Network) with two hidden layers and five neurons to predict CHF can reach 20 %, then the influences of thermal-hydraulic parameters on prediction of CHF were obtained based on this constructed ANN. Among the tens of CHF correlations, Tong's, Sudo's, and Mudawar's correlations were selected, and the results indicate that Sudo's correlation can forecast well in 1–4 MPa and Mudawar's correlation had relatively low prediction errors for a wide pressure range. The LUT (look-up table) needs proper correction factors to accurately predict the CHF in narrow rectangular channels.